Effectiveness of Chinese Betel Leaf Extract (Peperomia pellucida L) on the Growth of Propionibacterium acnes Bacteria - Mukhlisa, Ida; Juwita ZR, Juwita ZR; Dita, Sasmiati Farach (Journal of Health Science and Medical Therapy, 2025)
Propionibacterium acnes bacteria cause acne by producing lipase enzymes that break down free fatty acids in skin lipids. This study aimed to determine whether or not there is antibacterial activity from the extract of the Chinese betel leaf plant (Peperomia pellucida L) against Propionibacterium acnes and to determine the concentration of the inhibition zone. The study was experimental with 25%, 50%, 75% and 100% extract concentrations. The method used to test antibacterial activity in this study was the disc diffusion method, namely using discs planted on Nutrient Agar (NA) media. The maceration of Chinese betel leaves (Peperomia pellucida L) is the Chinese betel leaf extraction method. The results showed that at a concentration of 25% Chinese betel leaf extract, the results were 22.5 mm; at a concentration of 50% extract, the inhibition zone was 24 mm; at a concentration of 75% Chinese betel leaf extract, the inhibition zone was 30 mm, at a concentration of 100% Chinese betel leaf extract, the inhibition zone was 20 mm. The inhibition zone of the positive control using the antibiotic chloramphenicol was obtained at 10 mm; in the negative control using sterile distilled water, there was no inhibition zone. The results of the significance test of the Chinese betel leaf extract (Peperomia pellucida) from the Greenwood classification results in the Post hoc test show that the difference between concentrations can be stated as significant at each concentration.